Age-related deterioration of saccule-related neural function is associated with decreased estimated glomerular filtration rate and increased free thyroxine. Issue 5 (May 2019) - Jung, Ileok; Ahn, Su-Hyun; Lee, Juyoung; Lee, Sun-Uk; Oh, Hui Jong; Kim, Hyo-Jung; Choi, Jeong-Yoon; Kim, Ji-Soo
Highlights: Amplitude of cervical vestibular-evoked myogenic potentials (cVEMP) representing saccule-related neural function decreases with ageing. Decreased estimated glomerular filtration rate (eGFR) is associated with reduced cVEMP amplitudes. The deleterious effect of free T4 on cVEMP amplitude occurs in younger subjects but not in older ones. Abstract: Objective: This study attempted to identify systemic factors for age-related decline in neural function originating from the saccule using cervical vestibular-evoked myogenic potentials (cVEMP) parameters. Methods: We recruited 129 symptomatic vertiginous patients who did not have known disorder affecting the cVEMP pathway (mean age = 52.4 ± 13.9). The indicators of saccule-related neural function were the sum of normalized cVEMP amplitude (SNA) and the average of p13 latency on both sides (average latency, AL). Any associations between cVEMP and systemic factors were evaluated using a linear regression. Result: SNA decreased with ageing (p < 0.001) in univariable regression. The estimated glomerular filtration rate (eGFR) was positively associated with SNA (p = 0.002). Hematocrit, C-reactive protein, vitamin D, and free thyroxine (T4) showed a trend of association with SNA (p < 0.2). SNA was associated with ageing, increased free T4, and decreased eGFR in multivariable analysis. In the subgroup analysis, SNA was significantly associated with free T4 in younger patients (mean age = 41.5 ± 9.91) but not in the older ones (mean age = 63.5 ± 6.54). AL did not show any significant associations with systemic factors. Conclusion: Decreased eGFR and increased free T4 as well as aging may be risk factors for decline of saccule-related neural function. Significance: Neural function originating from the saccule may be affected by systemic factors.